|-48| = 48.
It is 12w = 48 or w = 4.
-4a = 48 a = -12
[ 2c2 + 10c - 48 ] is not a question. It's just an expression that stands for a number, and we can't tell what the number is until we know what 'c' is. If you said it was equal to something, then you'd have an equation, and you could ask "What number does 'c' have to be in order to make this equation true ?" But without an 'equals' sign ( = ) in it, it's not a question, and has no answer.
It is 48.
Lcm(32,48) = (32*48)/gcd(32,48)
If you make the unjustified assumption that the 25 people were a representative sample of the 600, then you would expect 48 sick people. However, that is merely the expected value, the true number is likely to be different from 48.
It is an equation in the form of: n/16 +7 = 10 and the value of n is 48
n/4=n-12 So n=4n-48 Therefore -3n=-48 Finally n=16
Presumably this is a simultaneous equation question in the form of: 3x+6y = 48 -5x+6y = 32 Subtract the bottom equation from the top equation in order to eliminate y. Note that 3x - - 5x is equal to + 8x: 8x = 16 Divide both sides by 8 to find the value of x: x = 2 Substitute the value of x into the original equations to find the value y: Therefore: x = 2 and y = 7
Range = highest value - lowest value Range = 60 - 48 = 12
-48 -16 = 20 First add -48 and -16, which = -64, which indicates that this is not an equation, because both sides are not equal. -64 â‰ 20
t - 17 = 48 The first step is to move the -17 to the right side of the equation and end up with: t = 48 + 17. (When you switch sides, the sign changes) To solve the equation: t = 65
42 over 48 equals 8 OR 42/48 = 8 is an incorrect mathematical equation.
% decrease = the absolute value of the difference of the original value and the new value divided by the original value multiplied by 100%% decrease:= |48 - 14|/48 x 100%= 34/48 x 100%= 0.7083 x 100%= 70.83%
The ascii value of zero - is 48.
x - 2 = 4x + 46-2 = 3x + 46-48 = 3xx = -48/3 or -16
First you have to transform the problem into equations.We have two unknow numbers, let's call them a and bthe sum of the two numbers if 72 would be writtena+b = 72their difference is 48 would be writtena-b=48(one of the number is greater than the other, we chose to say that a was the greatest)Now, we use the fact that we can add a same quantity to both part of an equation and keep this equation true. As a-b equals 48, it is the same quantity, and we can add it to both part of the equation a+b = 72. For the left part, with the unknown numbers, we add the part containing also unknow numbers (a-b) and for the right part (a value) we add the part with a value (48)a+b = 72 a+b+a-b = 72 + 48 a+a = 120 a = 60Now we have a. So we can substitute its value in any of the equations, for example the first who becomes60 + b = 72 60 + b - 60 = 72 - 60 (we add -60, a same quantity, to both side of the equation) b = 12(The mathematic reasoning to solve this problem have been shown in bold)
w2 - 13w + 48You want to write the equation in the form (w+a)(w+b). However, if this particular equation could be written in this form, there would be at least one value of x where y = 0. There are no such solutions for this equation, so it cannot be factored into this form.However, you can factor it if you separate 48 into 42.25 + 5.75:w2 - 13w + 48 = (w - 6.5)2 + 5.75 = (w - 6.5)(w - 6.5) + 5.75
what is value of an 1991 evinrude 48 hp outboard